A Gynecological Treatment Found in Qubbet el-Hawa and Described in Different Papyri - Jiménez-Serrano, Alejandro (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
The present paper discusses the finding of an hemispherical drinking cup between the heads of the femurs of a lady identified as Sattjeni A in a Late 12th Dynasty tomb in Qubbet el-Hawa, which has been catalogued as 34aa. The woman suffered a traumatic injury in her pelvis, which provoked her pain, sterility and iatrogenic pain. The presence of the ceramic with remains of organic material with evident signs of combustion is compared to similar treatments recorded in different papyri, one of them (P. Kahun) almost contemporary to the burial. The analysis of the textual sources has allowed us to relate this find to the medical treatments prescribed by the ancient specialists in the 12 th Dynasty.